Flat Feline Faces: Is Brachycephaly Associated with Respiratory Abnormalities in the Domestic Cat (Felis catus)? - Farnworth, Mark J; Chen, Ruoning; Packer, Rowena M. A.; Caney, Sarah M. A.; Gunn-Moore, Danièlle A. (PLOS ONE, 2016)
There has been little research into brachycephalism and associated disorders in cats. A questionnaire aimed at cat owners was used to determine the relationship between feline facial conformation and owner-reported cat management requirements and respiratory abnormalities. Owner-submitted photographs of cats were used to develop novel measures of skull conformation. One thousand valid questionnaires were received. Within these there were 373 valid photographs that allowed measurement of muzzle ratio (M%) and 494 that allowed nose position ratio (NP%). The data included 239 cats for which both measurements were available. Owners reported lifestyle factors (e.g. feeding type, grooming routine, activity level), physical characteristics (e.g. hair length) and other health characteristics of their cat (e.g. tear staining, body condition score). A composite respiratory score (RS) was calculated for each cat using their owner’s assessment of respiratory noise whilst their cat was asleep and then breathing difficulty following activity. Multivariate analyses were carried out using linear models to explore the relationship between RS and facial conformation, and lifestyle risk factors. The results showed that reductions in NP% and M% were significantly associated with RS (P < 0.001 and P = 0.026, respectively) and that the relationship was significantly negatively correlated (r = -0.56, P < 0.001 for both). Respiratory score was also significantly associated with increased presence of tear staining (P < 0.001) and a sedentary lifestyle (P = 0.01). This study improves current knowledge concerning cats with breeding-related alterations in skull confirmation and indicates that brachycephalism may have negative respiratory implications for cat health and welfare, as has been previously shown in dogs.